DAMPAK PERUBAHAN KONTRAK TERHADAP PELAKSANAAN PROYEK KONSTRUKSI DARI PERSPEKTIF KONTRAKTOR PADA PROYEK PENINGKATAN OBJEK WISATA AIR TERJUN TEKAAN TELU KOTA TOMOHON - Suhendra Gobel; Suhendra Gobel; Ir. Dr. Shirly S. Lumeno, ST, MT; Dr. Jefferey A. Delarue, ST, MT, (Sustainable Construction (SUSCON), 2024)
The development of the construction sector in Indonesia has experienced rapid progress over the past few decades, marked by various large infrastructure projects such as the construction of toll roads, airports, ports, and skyscrapers. Effective management of contract changes is crucial. One instance is the enhancement project of the Tekaan Telu Waterfall Tourist Attraction in Tomohon City, where various challenges such as difficult terrain and design changes have affected project implementation. This studyaims to identify the impact of contract changes on the implementation of construction projects from the contractor's perspective. The analysis results show that, in terms of construction indicators, design discrepancies are one of the causes of contract changes, with a percentage value of 78% or an average score of 3.9. For environmental indicators, slippery road access is a significant factor, with a percentage of 80% and an average score of 4.03. For resource indicators, almost all variables do not cause contract changes. In the additional causes or other reasons indicator, project delays are one of the causes of contract changes, with a percentage of 73% and an average score of 3.64. After identifying the causes, the study then analyzes the impact of contract changes from the time, quality, and cost indicators. For the time indicator, the highest percentage is 78% with an average score of 3.9, indicating that project delays significantly affect contract changes. For the cost indicator, the increase or decrease in work is one of the factors influencing contract changes, with a percentage of 62% and an average score of 3.2. For the quality indicator, material control is the most significant factor influencing contract changes, with a percentage of 73% and an average score of 3.63.